Acute myocardial infarction in post COVID-19 patients - Lombana Salas, Moisés Andrés; Miranda Jiménez , María Camila; Bedoya Coronel, Michelle; Herazo Madera, Wendy Yulieth; Lombana Salas, Enrique Arturo (International Journal of Medical Research and Review, 2021)
The SARS-CoV-2 infection has caused mortality in different populations; in addition, morbidity with immunological, hematological and/or cardiovascular compromises has been reported, with acute myocardial infarction (AMI) standing out. A literature search was conducted in databases to determine existing evidence regarding AMI in post-COVID-19 patients. It was found that initially AMI was described in some patients during the disease; however, a recently published case series showed that it could occur in recovered patients, secondary to systemic and procoagulant inflammation over time, suggesting further research in this area.